Determinants of technology adoption among Malaysian SMES: An IDT perspective - Ramayah, Thurasamy; Mohamad, Osman; Omar, Azizah; Marimu, Malliga (Universiti Utara Malaysia Press, 2013)
Traditional competitive advantages such as raw material availability, inexpensive labour and proximity to local markets are fast losing their importance to other factors such as technology adoption. In order to survive, it is imperative that organizations incorporate technology into their daily operations. Still, technological adoption and information and communications technology penetration among the Malaysian SME industry is yet to reach a much desired level. Hence, this paper aims to reveal the factors that drive technology adoption among SMEs in Malaysia using the perceived innovation characteristics outlined in the Innovation Diffusion Theory (IDT). Data was gathered from manufacturing and manufacturing-related services; SMEs scattered throughout the country and analyzed using the partial least squares technique. The analysis revealed that innovation characteristics such as perceived relative advantage, observability and image are positively-related to the adoption of a technology while compatibility and ease of use do not influence adoption. Interestingly, though trialability was found to have a significant impact on adoption, its effect turned out to be a negative one instead of a positive hypothesized relationship. The findings are further discussed and elaborated.